The arcuate nucleus of the C57BL/6J mouse hindbrain is a displaced part of the inferior olive - Fu, Y.; Watson, Charles (S. Karger AG, 2012)
The arcuate nucleus is a prominent cell group in the human hindbrain, characterized by its position on the pial surface of the pyramid. It is considered to be a precerebellar nucleus and has been implicated in the pathology of several disorders of respiration. An arcuate nucleus has not been convincingly demonstrated in other mammals, but we have found a similarly positioned nucleus in the C57BL/6J mouse. The mouse arcuate nucleus consists of a variable group of neurons lying on the pial surface of the pyramid. The nucleus is continuous with the ventrolateral part of the principal nucleus of the inferior olive and both groups are calbindin positive. At first we thought that this mouse nucleus was homologous with the human arcuate nucleus, but we have discovered that the neurons of the human nucleus are calbindin negative, and are therefore not olivary in nature. We have compared the mouse arcuate neurons with those of the inferior olive in terms of molecular markers and cerebellar projection. The neurons of the arcuate nucleus and of the inferior olive share three major characteristics: they both contain neurons utilizing glutamate, serotonin or acetylcholine as neurotransmitters; they both project to the contralateral cerebellum, and they both express a number of genes not present in the major mossy fiber issuing precerebellar nuclei. Most importantly, both cell groups express calbindin in an area of the ventral hindbrain almost completely devoid of calbindin-positive cells. We conclude that the neurons of the hindbrain mouse arcuate nucleus are a displaced part of the inferior olive, possibly separated by the caudal growth of the pyramidal tract during development. The arcuate nucleus reported in the C57BL/6J mouse can therefore be regarded as a subgroup of the rostral inferior olive, closely allied with the ventral tier of the principal nucleus.